Studi Awal Sintesis ZnO/SiO2 dengan Silika dari Limbah Padat Geothermal dan Uji Performansinya dalam Penghilangan Metilen Biru : Preliminary Study of ZnO/SiO2 Synthesis with Silica from Geothermal Solid Waste and Its Performance Test in Methylene Blue Removal - Joko Suryadi; Rahma Ardelia Raissa; Teguh Aditya Nugraha; Nirmala Utami; Paramitha, Tifa (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Industrial development impacts environmental problems, such as the emergence of wastewater containing methylene blue. In this research, SiO2 was composited with ZnO to remove methylene blue. The steps of this study include SiO2 extraction from geothermal solid waste, ZnO/SiO2 synthesis, and methylene blue removal test. The process of extracting SiO2 from geothermal solid waste used the sol-gel method. The FTIR analysis showed that SiO2 contains siloxane group (Si-OH) and silanol group (Si-O-Si). ZnO/SiO2 synthesis was done by making SiO2 suspension and continued with adding the addition of several Zn(NO3)2.6H2O. The FTIR analysis of ZnO/SiO2 showed no absorption at the wavenumber 960 cm-1 and there is a shoulder around the number 950 cm-1 which indicates the vibration of Si-O-Zn. Meanwhile, methylene blue removal tests were carried out on artificial wastewater. Based on the research results, the highest percent removal (99%) was obtained under operating conditions, including a dose of 500 mg/L, pH 10, and contact time of 30 minutes. Based on box-benkhen analysis, it is known that dose and pH singularly affect the percent removal, while contact time does not affect the percent removal. The optimization results obtained optimum conditions for methylene blue removal at a dose of 581.952 mg/L, pH of 10, and contact time of 30 minutes. Percent removal in conditions without irradiation and with irradiation of UV light were 98.758% and 99.178%. It shows that the adsorption process is the main process in removing methylene blue, while the photocatalytic process has little effect because it is possible that only a small amount of ZnO can attach to the surface of SiO2.